Reception of Kajkavian Poetry by Štefan Modrinjak - Ditmajer, Nina (Slavia Centralis, 2024)
The article focuses on two poems by Štefan Modrinjak and presents the past Croatian literary tradition that influenced the creation of his poems. The poem Od protuletja/On Spring traces the Baroque Kajkavian poetic tradition that has been preserved in manuscript and oral traditions for at least two centuries, while his Molitva na Božico Slovenko/Prayer to the Slovenian Goddess was influenced by printed works of prose and poetry from the Croatian Renaissance, Baroque and Enlightenment periods.
Keywords: Štefan Modrinjak, Kajkavian literature, manuscript hymnals, Croatian literature, literary reception